Social class, politics, and urban markets : the makings of bias in policy outcomes - Boschken, Herman L. (Stanford University Press, 2002)
"This book is about the policymaking of public agencies in large American cities. Based on a decade of research, it studies urban mass transit in terms of the factors that bias the industry's policy outcomes to benefit one public or another. Why is there a great variance of outcomes among agencies? What are the important taproots of bias in policymaking? How does the pattern of outcomes correspond to the American mosaic of public interests?" "The book's second - broader and more important - purpose is to demonstrate the value of social science theory in making sense of urban processes and the responsiveness of governmental policymaking in a plural society. The book analyzes the applicability of six rival theses - derived from political science, economics, administrative theory, sociology, social psychology, and urban planning - to understanding the forces that mold policymaking in American metropolitan areas."--Jacket